Epistemologies of Making: A theory of craftsmanship for architecture - Crevels, Eric (A+BE | Architecture and the Built Environment, 2024)
This research addresses how different ways of making entail different ways of knowing, exploring how material production and knowledge intersect and inform one another. Specifically, it investigates the knowledge within crafts — examining how skill is developed in the way craftspeople work – and hypothesises that the material and social conditions surrounding craft practice produce a specific rationality: a process-oriented way of knowing. These considerations are brought together in a theory of knowledge in the material productions – an epistemology of making – whose tenets are subsequentially tested within the field of architecture. Through this set of conceptual and theoretical tools, the research thus analyses the dynamics of knowing and making in architecture. Ultimately, this study reflects on the implications of approaching architecture from the vantage point of its production, offering valuable insights into the dialectics of design and construction.